Preface to stable isotopes in hydrological studies in the tropics: Ecohydrological perspectives in a changing climate - Sánchez Murillo, Ricardo (2019)
Tropical regions (comprised between the Tropics of Cancer and Capricorn, 23.5°N to 23.5°S) cover approximately 36% of the Earth's landmass. They are home to 40% of the world's population, which is projected to increase over 50% by 2030 (State of the Tropics, 2014). During the last decade diverse scientific disciplines, environmental institutions, governments, and stakeholders have increased awareness of the importance of current tropical climate variability and the associated ecohydrological and societal responses (González, Georgescu, Lemos, Hosannah, & Niyogi, 2017; Wright et al., 2018). On the basis of the premise that warming‐related changes in regional and global circulation patterns will affect tropical precipitation (Chou & Neelin, 2004) and may lead to an intensification of extreme events (i.e., an increase in tropical cyclone intensities, unprecedented floods, and severe droughts; Meehl et al., 2000; Walsh et al., 2016), risk management and water resources management in the tropics represent a major challenge (Seneviratne et al., 2012). The global distribution of rainfall depicts maximum values in the tropics, where the incoming solar radiation peaks and the largest concentration of atmospheric water vapour is observed at a deeper tropopause. However, as the tropical belt is mostly covered with oceans, precipitation is not easy to monitor. Tropical ecohydrological conditions are usually under the influence of complex land–ocean– atmosphere interactions (Esquivel‐Hernández, Sánchez‐Murillo, Birkel, Good, & Boll, 2017; Wilcox & Asbjornsen, 2018) that produce a dynamic cycling of mass and energy composed of water vapour mixing ratio distributions, cloud formation mechanisms, precipitation and convergence, ecohydrological connectivity and services, groundwater recharge processes in complex aquifers, runoff generation, rapid land use changes, and vegetation dynamics